Integrative approach reveals the identity of Brazilian specimens previously recognized as Anastrepha dissimilis Stone, 1942 (Diptera: Tephritidae) - Araújo, Alexandre S.; Zucchi, Roberto A.; Norrbom, Allen L.; Nanini, Frederico; Corrêa, Alberto S.; Alvarenga, Clarice D.; Souza-Filho, Miguel F.; Nava, Dori E.; Savaris, Marcoandre (Zootaxa, 2023)
Anastrepha dissimilis is currently considered to be widely distributed in Brazil, occurring in 20 of 27 states. However, morphological differences between the holotype (from Plaisance, Haiti) and a paratype (from Pernambuco, Brazil) suggest that the Brazilian specimens are not A. dissimilis, because their aculeus tip is similar to the paratype not to the holotype. Therefore, considering the importance of integrative taxonomy for species delimitation, we used geometric and linear morphometrics and cytochrome c oxidase subunit I sequences integrated with the morphology of the aculeus tip to clarify the identity of populations previously identified as A. dissimilis from multiple Brazilian localities. Morphological data show a uniform pattern among the Brazilian populations, with some variation among specimens from the south and northeast. In addition, the geometric and linear morphometrics suggest considerable geographic variation among these populations, suggesting the existence of at least two morphs. The molecular analysis revealed that specimens from Brazil previously identified as A. dissimilis belong to Anastrepha chiclayae Greene, with a genetic distance ranging from 0.00 to 0.015%. According to our integrative analyses, specimens from Brazil formerly identified as A. dissimilis actually are A. chiclayae. Therefore, this is the first record of A. chiclayae in Brazil, and we also report that A. dissimilis does not occur in Brazil.